2013
DOI: 10.1063/1.4791568
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of superlattice of microcrystalline silicon carbide layers for photovoltaic application

Abstract: We have systematically studied a series of silicon carbide multilayer (#SiC) samples, each consisting of 30 periods of two alternating layers of microcrystalline silicon carbide (lc-SiC:H) having identical band gap of 2.2 eV but different amount of crystalline silicon volume fraction. The thickness of the lc-SiC:H layer deposited at higher power (termed as HPL) with higher degree of crystallinity was kept fixed at a value of 5 nm, while the thickness of the other lc-SiC:H layer deposited at a lower power (term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The 2.1 eV peak has been observed in our earlier stuy on µc-SiC:H superlattice samples. 6 We explained this peak on the basis of a radiative tunneling between the band tail states as occurs in a-Si:H. 33 The origin of the 2.1 eV PL peak may also arise in this case from a defect state in SiO 2 . 34 The lower energy peak at 1.8 eV may be due to the nc-Si grains showing confinement effect.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The 2.1 eV peak has been observed in our earlier stuy on µc-SiC:H superlattice samples. 6 We explained this peak on the basis of a radiative tunneling between the band tail states as occurs in a-Si:H. 33 The origin of the 2.1 eV PL peak may also arise in this case from a defect state in SiO 2 . 34 The lower energy peak at 1.8 eV may be due to the nc-Si grains showing confinement effect.…”
Section: Discussionmentioning
confidence: 96%
“…[2][3][4] Regular arrangement of Si-QDs may be achieved by the formation of superlattices of the Si-QD layers sandwiched between layers of dielectric. Si-QD solar cells have been described by forming superlattice of Si-QDs with amorphous silicon 5 or amorphous silicon carbide 6 used as the absorbing layers with controllable band gap. However, due to low band gap of 2.5 eV for SiC in comparison with Si 3 N 4 (∼5.3 eV) or SiO 2 (∼9 eV), the Si-QD / SiC barrier height is also low.…”
Section: Introductionmentioning
confidence: 99%
“…The deposition time for the LPL/HPL layer in each cycle were controlled in order to get the desired thickness (Table 2) as per the known growth rates ( Table 1). The individual thicknesses of the HPL and LPL layers were acquired from ellipsometric measurements [21] and indicated in Table 2. For one sample (#SiC-ML4), the overall thickness has been verified by the cross sectional TEM measurement as will be discussed later in Section 3.…”
Section: Methodsmentioning
confidence: 99%
“…In this respect, low temperature growth of high quality amorphous or microcrystalline group IV materials (Si, Ge, C) and their alloys by PECVD method has prompted many researchers to study superlattice/multilayers of these materials [20]. In our previous studies, we have demonstrated the photovoltaic effects of Si-QD embedded hydrogenated silicon carbon alloy (SiC:H) multilayers consisting of the alternating layers of a nearly amorphous silicon carbide (a-SiC:H) and a microcrystalline silicon carbide (c-SiC:H) containing high density of Si-QDs grown at low deposition temperatures (~ 200C) in a PECVD system [21]. We also studied the structural properties such as crystalline volume fraction of Si, voids, PL response in a series of such multilayers [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation